The role of the english language in providing information and in tourism education : City of Cuenca 2006-2007 - Flores Cordero, Piedad (2007)
We will begin the final report of the project with the documental research and particulary the field resarch by displaying the quantitative information by means of satistical ans graphic representation. The analysis of the results will be done in chapter 4. The field investigation was done during the omths of january and february of 2007 it consisted of t he structrured interviews in accordance with the objetives and directed to foreign tourist focusing on the role that english plays as an main hypothesis of information and communication. Total number of interviews was thirty nine that covered places of torust interest and also the most representative insitutions of the City . Mentioned interviews include fifteen foreign touris, eight travel agencies forus museums there univessties inclllude fifteen foreing tourist eight travel eight travel angecies four museums, threee universties four artesian centers, four tourist